Taxonomy of ’Euconnus complex’. Part IV. Review of Euconnus subgenus Rhomboconnus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Morphological structures of the type species of Euconnus (Rhomboconnus Franz) are described and illustrated, and compared with those of Euconnus s. str. Rhomboconnus, although showing several peculiar character states (e.g., rudimentary or lacking basal elytral foveae) is maintained as a subgenus of Euconnus, and its revised diagnosis is given. Two species currently placed in Rhomboconnus, E. perplexus Franz (Venezuela) and E. trianguliceps Franz (Ecuador) are redescribed. A surprising and striking similarity of the aedeagus of Rhomboconnus to that of Plaumanniola Costa Lima (Plaumanniolini) is discussed as yet another structural evidence supporting a previously postulated close relationship between the enigmatic Plaumanniolini and the ’Euconnus complex’.